Gambaran pengetahuan masyarakat terhadap pemakaian gigi tiruan di kota kendari (kajian pada rsud bahteramas kendari) - Qasrini Zatil Ilham; Suzan Elias (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Teeth are one of the most important parts of the mouth which play a role in speech and mastication. Teeth and mouth are the 'gateways' where microorganisms enter which can affect the health of other organs of the body. Currently, although dentistry science and technology makes it possible to prevent tooth decay as early as possible, there are still many cases of tooth loss that affect a decrease in the effectiveness of mastication which indirectly affects a person's overall health. Loss of teeth can also have emotional and functional impacts and can affect aesthetics. Tooth loss is a condition where one or more teeth are released from their socket or place, which is caused by trauma, caries and periodontal disease. To overcome this problem, prosthodontic treatment is useful to restore and maintain the function of the teeth by making dentures. Dentures are divided into two types, namely removable dentures and fixed dentures (GTC). Removable dentures consist of complete dentures (GTL) and removable partial dentures (GTSL), while fixed dentures are bridge dentures and denture crowns. Objective: This study aims to describe the public's knowledge of the use of dentures at Bahteramas Hospital, Kendari city. Methods: This type of research is a descriptive observational study with a cross-sectional design. The study was conducted by distributing questionnaires consisting of 18 questions regarding dentures. Results: The results of this study indicate that almost all respondents have good knowledge about the use of dentures in general. Conclusion: Overview of Public Knowledge of Denture Use in Kendari City, it can be concluded that they have a good level of knowledge.